Putting the stress on conspiracy theories: Examining associations between psychological stress, anxiety, and belief in conspiracy theories. (September 2016) - Swami, Viren; Furnham, Adrian; Smyth, Nina; Weis, Laura; Lay, Alixe; Clow, Angela
Abstract: Psychological stress and anxiety may be antecedents of belief in conspiracy theories, but tests of this hypothesis are piecemeal. Here, we examined the relationships between stress, anxiety, and belief in conspiracy theories in a sample of 420 U.S. adults. Participants completed measures of belief in conspiracy theories, perceived stress, stressful life events, trait and state anxiety, episodic tension, and demographic information. Regression analysis indicated that more stressful life events and greater perceived stress predicted belief in conspiracy theories once effects of social status and age were accounted for (Adj. R 2 = .09). State and trait anxiety and episodic tension were not significant predictors. These findings point to stress as a possible antecedent of belief in conspiracy theories. Highlights: More stressful life events predicted belief in conspiracy theories. Greater perceived stress predicted belief in conspiracy theories. State and trait anxiety and episodic tension were not significant predictors.